تأثير نسبة السيليكات إلى النترات في نمو المشطورات لمحطتين من الجزء الشمالي للمياه الشاطئية لمدينة اللاذقية - درويش, فيروز; حسن, مهند (Latakia University Journal -Biological Sciences Series, 2013)
يوضح هذا البحث قدرة نمو العينات الطبيعية للمشطورات تحت نسب Si:Nالطبيعية خلال شهر آذار في عام 2010. بالإضافة لذلك تم البحث في إمكان حدوث تغيرات في العوامل المحددة للنمو وتغيرات في سيادة مجموعات العوالق النباتية من المشطورات إلى ثنائيات السياط. لذلك تم جمع عوالق العينات من محطتين بحريتين مختلفتين بخصائصهما البيئية، في تجارب التغذية لدراسة سلوكية المشطورات تحت نسب Si:N مختلفة (Si:N=0.3, 7). تبين أن المشطورات تمكنت من النمو في النسب Si:N المنخفضة (Si:N=0.3) والمرتفعة (Si:N= 7 ) في التجارب المنجزة في كلا المحطتين المدروستين. و يتفوق نمو المشطورات على نمو ثنائيات السياط. لم يلاحظ أي تغير في العوامل المحددة لنمو المشطورات من النترات تجاه السيليكات في القوارير ذات الـنسب Si:N المنخفضة، وبالتالي لم يسجل أي تغير في نمو المشطورات تجاه ثنائيات السياط. أثرت تجارب التغذية في التركيب النوعي للمشطورات، حيث ساد النوع Nitzschia closterium Ehrenberg، وهو من الأنواع غير الشائعة خلال الإزهرار الربيعي للعوالق النباتية في المحطات المدروسة. Experiments were carried out at two stations in the northern part of Latakian coastal water during March 2010, to investigate the influence of Si: N ratios on diatoms growth and to determine the conditions that would generate Si limitation in diatom growth and that might cause a shift from diatom to din flagellate dominance. To achieve that, Natural Phytoplankton were cultured in mesocosm experiments. At the beginning of the experiment, the inorganic nutrients were manipulated to give different inorganic Si: N ratios (ranged between 0, 3 and 7). The results showed that Diatoms were still dominant under these Si: N ratios and Din flagellates remained unaffected, regardless of the above different ratios. The experiment did not show any Silicate limitation to the diatom growth even under the lowest N: Si ratios. Moreover, the species composition of diatoms was affected by the enrichment experiments operated in two stations. Here, the Nitzschia closterium species dominated under both low and high Si: N ratios although their occurrence is not common during the spring phytoplankton bloom at both sites.